Pengaruh Komunikasi Internal Terhadap Efektivitas Kerja Pegawai Kecamatan - Haprilwanti, Nenden; Hikmawati, Ikeu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this research is to find out how internal communication influences the work effectiveness of employees in Karang Tengah District, Garut Regency. The research uses descriptive methods with survey techniques with emphasis on the concept of measuring internal communication according to Davis & John W Newstrom and measuring employee work effectiveness according to Jamin. The research population was 30 sub-district employees, all of whom were used as respondents using census techniques. The data collection techniques used were observation, questionnaires, interviews and literature study. The research results show that there is a significant influence of internal communication on employee work effectiveness. This can be seen from the large influence of internal communication variables on employee work effectiveness of 47%, while the remaining 53% is influenced by other factors including employee work motivation. Suggestions that can be put forward are for leaders to frequently interact directly with employees, either through face-to-face or casual chatting, so that employees feel cared for, providing information regularly by maximizing the various communication media that are available. Leaders should continuously develop employees' technical abilities, leaders should make clear reward and compensation provisions so that they can motivate employees to work without just doing tasks without responsibility so that the amount of work can be as targeted and completed on time.